Smartstrap Accessories Untuk Monitoring Kondisi Pasien Covid-19 saat Karantina Mandiri Berbasis Internet of Things - Yoga Kholilul Akbar Pradana S; M. Abdullah Anshori; Abdul Rasyid (Jurnal Jaringan Telekomunikasi, 2021)
The world is being hit by an outbreak of the Coronavirus Disease 2019 (COVID-19) pandemic in 2021. The number of Covid-19 cases continues to increase, especially in Indonesia itself, the number of Covid-19 sufferers is not proportional to the number of health workers. This tool aims to make simple accessories that are used to unite the conditions of patients infected with Covid-19 while undergoing independent activities, as well as being one of the efforts to implement social distancing. Based on tests conducted on 5 samples of people as patients, temperature measurements using the MLX90614 infrared sensor showed an average error of 0.12°C after being calibrated using a digital infrared thermometer. While the measurement of the pulse sensor MAX30100 after being calibrated with Oxymeter SO911 has an average error of 0.52 BPM in measuring heart rate in measuring oxygen saturation in the blood, showing an average error of 0.6%. For the Quality of Service (QoS) test results, the throughput value is 13,840 Kbps, packet loss is 0%, the average delay is 124,08649 ms and the jitter is 162.2 ms.